Functional traits of avian frugivores have shifted following species extinction and introduction in the Hawaiian Islands. (19th September 2020) - Case, Samuel B.; Tarwater, Corey E.
Abstract: The extinction and introduction of species can alter ecological processes owing to the loss or gain of species roles. In vertebrate‐dependent seed dispersal, mutualisms between frugivores and fruiting plants depend, in part, on matching of functional traits. High species turnover of frugivores has occurred on the Hawaiian Islands, owing to both the loss of native frugivores and the introduction of a new suite of frugivores. How this turnover has altered the functional traits of frugivores and the potential impacts on seed dispersal remain unclear. We investigated how avian frugivore traits differed between historic and modern assemblages of the Hawaiian Islands. We also tested how traits shifted within foraging guilds (ground vs. arboreal) to distinguish potential impacts on plants within low versus high forest strata. Compared to historic frugivores, the modern assemblage is smaller in gape width and body mass in both ground and arboreal guilds. Wing shape did not significantly change between assemblages. From the results, we postulate that changes in the frugivore community have likely altered seed dispersal processes by reducing (a) the size of seeds consumed, (b) frugivory rates per animal and (c) seed dispersal distances. Owing to seed size placing strong constraints on consumption, we reviewed recent studies on frugivory by modern birds in the Hawaiian Islands and compared the size of seeds consumed versus seeds available. We found that larger‐seeded plants (>8.1 mm seed width) were not consumed by modern birds and were more likely to be of conservation risk compared to smaller‐seeded plants. Consequently, dispersal limitation may threaten Hawaiian plant communities, with larger‐seeded plants at greatest risk of extinction. Broadly, we show that extensive turnover within assemblages may lead to significant changes in functional traits, with potential knock‐on effects for mutualistic interactions and communities. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.